Implementation of herd health program to improve survival of Boer goats in Malaysia. - Salisi, Mohd Shahrom; Saad, Mohd Zamri; Kasim, Azhar (Springer Verlag, 2012)
A Boer goat breeding farm with 800 heads of breeder females, 50 breeder males, and 400 growing goats of various ages in Sabah, Malaysia was selected to study the effect of implementing herd health program. This included vaccination program against pneumonic mannheimiosis; fecal monitoring for helminthiasis, coccidiosis, and colibacillosis; and introduction of modified feeding regime comprised of day-time grazing and feeding of cut grass and supplemented feed. The herd health program was implemented in September 2007 and the impact was observed on body weight gains, body scoring, and annual mortality among adults and kids. It was found that implementation of herd health program significantly (p<0. 05) increased the average body weight gains in both adults and kids from 1. 8 g per kid and 0. 6 g per adult in 2006 to 3. 7 g per kid and 2. 2 g per adult in 2008. The percentage of adults with body scoring of <3 was significantly (p<0. 05) reduced from 82. 3% in 2006 to 77. 6% in 2007 and 4% in 2008. Similarly, the annual mortality rate was significantly (p<0. 05) reduced from 6. 5% among kids and 58. 2% among adults in 2006 to 12. 1% among kids and 10. 4% among adults in 2007, and to 9. 1% among kids and 1. 1% among adults in 2008. Therefore, it was concluded that implementation of herd health program significantly improved the survival and performance of goats.